Site-specific nutrient management improves soil quality in an ultisol under continuous cassava cultivation - G. Byju; R. Shiny (JOURNAL OF ROOT CROPS, 2023)
The study aimed to assess the impact of fertilizer applications on soil properties and compute soil quality index (SQI) in a laterite soil under cassava cultivation. The treatments comprised N omission, P omission, K omission, NPK omission, present recommendation (PR) and site-specific nutrient management (SSNM). Soil physico-chemical and biochemical properties were estimated and, selected minimum data set through principal component analysis and soil quality index were developed. Radar diagram was plotted to find out the limiting parameter and correlation between SQI and crop yield was studied. Soil properties such as pH, organic C, labile C, available N, P, K, Ca, Mg, Fe, Mn and Zn showed significant difference among the treatments. SSNM resulted in significantly higher pH (4.60), labile carbon (0.143%), available N (214.82 kg ha-1), Ca (119.70 ppm), Mg (156.15 ppm), Fe (10.20 ppm) and Zn (13.51 ppm) contents. PR treatment showed significantly higher content of organic C (1.17%) and available P (248.44 kg ha-1). Available K and Mn were significantly higher in N omission (472.92 kg ha-1) and NPK (47.80 ppm) omission treatment respectively. Normalised SQI was significantly highest for SSNM (0.86), followed by PR (0.73) and lowest for N omission (0.54), followed by P omission (0.55). No significant correlation was observed between crop yield and SQI. The study indicated that SSNM resulted in improvement of soil quality as revealed from higher SQI.